PENGARUH METODE PBL BERBASIS MIND MAPPING TERHADAP HASIL BELAJAR IPA SISWA KELAS VI SDN 1 SETROJENAR - Kiki Karnila Widiastuti; Istiqomah Istiqomah; Ana Fitrotun Nisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to analyze the application of the mind mapping-based PBL model to student learning outcomes using Classroom Action Research (PTK). This research consisted of two cycles with the subjects of this research being class VI students at SD Negeri 1 Setrojenar consisting of 18 students. This research design uses a quantitative approach with research instruments, namely observation sheets and pretest and posttest questions to see the success of using the mind mapping-based PBL learning model. The research results show an increase in student learning outcomes in the cognitive aspect, namely an increase in learning outcomes. Furthermore, the affective aspect is a change in student behavior, which is more active and has higher learning motivation. The psychomotor aspect shows an increase in students' skills in using Canva media to create mind maps.